Down by the River: Design for Organising. (5th September 2018) - Shin, Jae; Rich, Damon
Abstract : Design is not always about imposing creativity; sometimes vision is the problem! Finding ways to weave together conflicting agendas can be precisely what brings energy to a project – as with the new riverfront park for Newark, New Jersey.Jae Shin and Damon Rich, who lead the Newark‐based urban design studio Hector, describe how it came about: from negotiations with the local mayor, the US Army Corps and environmental advocates, to community engagement work with neighbourhood organisations.